The rare Ogilvie’s syndrome during pregnancy with scrub typhus and dengue co-infection - Nazreen; B., Hiremath P.; Sekar, Sindhujha; Kalaivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ogilvie’s syndrome is a syndrome characterized by symptoms suggestive of intestinal obstruction without any mechanical cause. Otherwise known as acute colonic pseudo-obstruction (ACPO). This condition is very uncommon, however it is very important to recognize it at the earliest, as it increases the risk of mortality and morbidity if left untreated. It is mostly seen post traumatic or post operative. Though commonly seen associated with post caesarean section, rarely seen during the period of pregnancy. The treatment is fundamentally conservative, but the need of surgical management has also been reported in severe cases. Here, we describe the rare Ogilvie’s syndrome in young pregnant term female that continued to progress despite appropriate treatment.